Miniaturized ultra wide band multiple input multiple output wearable antenna as wireless body area network for breast cancer detection - Mahmood, Mahmood Sarmad Nozad (2022)
Breast cancer is one most vital and spread diseases among women nowadays. Various techniques and methods have been applied to detect and cure this disease with the most minor side effects on the body, such as Magnetic Resonance Imaging, Chemotherapy, Radiotherapy, and so on. However, each of these methods indicated some drawbacks, like being blocky, having difficulty with mobility, and being present at the clinic for diagnosis. Wearable systems minimize the dimensions of the rigid printed circuit board (PCB) carrying the electronics and feeding the textile antenna for health monitoring applications. In on-body applications, most sensor antennas are bulky (the present antenna systems showed lower performance with larger dimensions), costly, low performance, and send patients’ data with the help of personal computers (PC) located in the patients’ homes, which is non-wearable. These wearable electronics should interact with the physical environment as smoothly as possible and be protected in hostile environments against mechanical damage and harsh environments. The excellent robustness and flexibility are crucial components that can provide health monitoring systems with the capability of continuously tracking vital signals of the human body with comfort. However, the antenna’s performance is degraded in the proximity of the human body. A low-cost, low-profile modified antipodal four terminal Multiple Input Multiple Output (MIMO) Ultra Wide Bnad (UWB) antenna is proposed offering a good radiation performance (miniaturized, high directive gain, and high fidelity). It presents a detachable electrical connection, reduces the risk of infection, and decreases time and costs significantly. It also eliminates the need for a PC to monitor the body locations. The design is fabricated, and the simulation and measured results are matched well, proving the validity of the new concept. It could monitor the human breast in real-time. The wearable UWB MIMO antenna’s performance was demonstrated in free space and on body locations at different distances, calculating the reflection coefficient (S11), bandwidth (BW), gain, and efficiency. It is demonstrated that the UWB MIMO antenna provided a good impedance bandwidth (S11< −10dB), with high stability in radiation pattern, efficiency, gains, and free space and on-body. Meanwhile, the UWB MIMO has a Specific Absorption Rate (SAR) under the standard limits for both 1g (<1.6W/Kg) and 10 g tissues (<2W/Kg) in flat and bending situations. Furthermore, the proposed UWB imaging system can detect a tumour with a diameter of less than 5 mm in any location within the breast with the most clutter removal. The concept of detectability of UWB MIMO design offers passive, low-cost, and versatile system reconfigurability, which can benefit wearable applications. In addition, our proposed approach provides a wide range of benefits in various applications when a PC is not always needed. Thus, the solution presented is robust, affordable, flexible, and allows for the extension of the scope of monitoring body locations easily.